2022
DOI: 10.1111/jnc.15737
|View full text |Cite
|
Sign up to set email alerts
|

Use of metabolic glycoengineering and pharmacological inhibitors to assess lipid and protein sialylation on cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In the early years of MGE, most experiments were performed with human cancer or rodent cell lines, which readily accommodate sugar analog incorporation (Du et al., 2009; Keppler et al., 2001). Although a simplistic explanation, we observed that facile MGE labeling of cells was correlated with rapid cell proliferation (Jones et al., 2004; Yarema, 2002), which requires constant production of membrane components that host metabolically labeled glycans in both glycoproteins and glycolipids (Kayser, Geilen et al., 1992; Kranaster et al., 2022). Over time, MGE has expanded on many fronts to augment cell behavior, target intracellular and even extracellular components such as extracellular vesicles, serve as imaging agents, and improve the production of therapeutic proteins (Agatemor et al., 2019; Buettner et al., 2018; Dammen‐Brower et al., 2022).…”
Section: Strategic Planningmentioning
confidence: 99%
“…In the early years of MGE, most experiments were performed with human cancer or rodent cell lines, which readily accommodate sugar analog incorporation (Du et al., 2009; Keppler et al., 2001). Although a simplistic explanation, we observed that facile MGE labeling of cells was correlated with rapid cell proliferation (Jones et al., 2004; Yarema, 2002), which requires constant production of membrane components that host metabolically labeled glycans in both glycoproteins and glycolipids (Kayser, Geilen et al., 1992; Kranaster et al., 2022). Over time, MGE has expanded on many fronts to augment cell behavior, target intracellular and even extracellular components such as extracellular vesicles, serve as imaging agents, and improve the production of therapeutic proteins (Agatemor et al., 2019; Buettner et al., 2018; Dammen‐Brower et al., 2022).…”
Section: Strategic Planningmentioning
confidence: 99%